2006
DOI: 10.1002/ptr.1981
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of fat storage in mice fed a high‐fat diet long term by treatment with saponins prepared from Kochia scoparia fruit

Abstract: The fresh fruit (Japanese name, Tonburi) of Kochia scoparia has been used as a food garnish in Japanese-style dishes from ancient times, and may prevent metabolic syndromes such as hyperlipidemia, hypertension, obesity and atherosclerosis. This study was performed to clarify whether an ethanol extract of K. scoparia fruit prevented obesity induced in mice by a high-fat diet for 9 weeks. The ethanol extract of K. scoparia fruit prevented the increases in body weight and parametrial adipose tissue weight induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 12 publications
1
26
0
3
Order By: Relevance
“…4). Many authors have shown that saponins can also reduce triglycerides in plasma, but the mechanism is not yet elucidated (Ebaid et al, 2006;Francis, Kerem, Makkar, & Becker, 2002;Gee & Johnson, 1988;Han et al, 2006;Milgate & Roberts, 1995;Oakenfull, 2001;Uemura et al, 2011;Wang et al, 2012). Previous studies in rats and BALB/c mice showed an increase in visceral fat after a long-term diet high in refined carbohydrates (Fortino et al, 2007;Oliveira et al, 2013).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…4). Many authors have shown that saponins can also reduce triglycerides in plasma, but the mechanism is not yet elucidated (Ebaid et al, 2006;Francis, Kerem, Makkar, & Becker, 2002;Gee & Johnson, 1988;Han et al, 2006;Milgate & Roberts, 1995;Oakenfull, 2001;Uemura et al, 2011;Wang et al, 2012). Previous studies in rats and BALB/c mice showed an increase in visceral fat after a long-term diet high in refined carbohydrates (Fortino et al, 2007;Oliveira et al, 2013).…”
Section: Resultsmentioning
confidence: 94%
“…are very rich in steroidal saponins (Challinor et al, 2012). The ability of this kind of saponins to form insoluble complexes with cholesterol, promoting their fecal elimination and causing a hypocholesterolemic effect is well known (Ebaid et al, 2006;Han et al, 2006;Sidhu & Oakenfull, 1986;Uemura et al, 2011;Wang et al, 2012). Despite be not yet chemically defined, species of Herreria belongs to Agavaceae family that are also rich in steroidal saponins (Romuald et al, 2013).…”
Section: Resultsmentioning
confidence: 95%
“…This pancreatic lipase inhibitory phytochemicals include mainly, polyphenols, flavonoids, saponins and caffeine [136][137][138][139]. Many carbohydrates also possess potent PL inhibitory effects [140,141].…”
Section: Inhibitory Effect On Pancreatic Lipase Enzymementioning
confidence: 99%
“…Another study also reported active compounds that have the potential to inhibit the activity of the pancreatic lipase is a saponin contained in plant Theasinensis (Han et al, 2001) and Platycodi radix (Xu et al, 2005), Panax japonicas , Kochiascoparia (Han et al, 2006) and falvonoid contained in the leaves of Dutch identity (Darusman et al, 2001). Pancreatic lipase activity increases, it will increase the absorption of monoglycerides and fatty acids that affect obesity (Joshita et al, 2000).…”
Section: Lipase Enzyme Activitymentioning
confidence: 99%